Cerebral vasospasm resulted in "stent shortening" after pipeline assisted coil embolization for blood blister aneurysms. Issue 33 (20th August 2021) - Wang, Ting; Richard, Seidu A.; Li, Junrao; Jiao, He; Zhang, Changwei; Wang, Chaohua; Lin, Sen; Xie, Xiaodong; You, Chao
Abstract : Abstract: Blood blister aneurysms (BBAs) are intracranial arterial lesions appearing in nonbranching sites of the supraclinoid internal carotid artery as well as the basilar artery. Endovascular treatment of BBAs is still not well established because of the rarity of these lesions. We report incidences of BBAs with associated vasospasms. Treatment of the BBAs and associate vasospasms with single Pipeline Flex embolization device (PLED) assisted coiling resulted in seemly shorting of the PLEDs in 3 patients. A retrospective analysis of patients with BBAs who were treated with single PLED assisted coiling from July 2018 to October 2019 was conducted. Patients' ethnic and medical records, aneurysmal characteristics, intraoperative-rupture, cerebral vasospasm (CVS), postprocedure contrast filling, follow-up imaging, and results were analyzed. Neurological examination at baseline and outcome based on modified Rankin scale (mRS) at discharge as well as follow-ups were also documented. Six patients consisting of 5 females and 1 male, with a mean age of 48.3 years (range from 34–67) were identified during our analysis. All the BBAs were located in nonbranching site of supra-clinoidal segment of internal carotid artery with a mean neck width of 4.5 mm and mean aneurysm size of 4.23 mm. PLED assisted coiling's were performed in all of them. CVS was observed in 3 patients while 1 patient had an intraoperative-rupture of the BBA. Postprocedure contrast filling was still present in 1 patient. All the patients had good outcomes with discharge and follow-up mRS scores ≤ 2 except 1 patient with mRS score = 3 with aphasia. PLED assisted endovascular coiling is very safe and efficient in treating patients with BBAs. Resolution of CVSs after treatment made the PLEDs seemly shorter. Furthermore, a combination of arterial lengthening after gaining their tensile strength back and radical expansion of the PLED could account for the shortening.